2019
DOI: 10.1016/j.urology.2018.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pressure Regulating Balloon Exchange in Men With Post Artificial Urinary Sphincter Persistent or Recurrent Stress Urinary Incontinence

Abstract: PRB exchange can transiently alleviate persistent or recurrent post-AUS SUI in the absence of mechanical failure or urethral pathology. Caution is warranted in patients with prior radiation as this was a risk factor for urethral erosion. Although many patients may require device revision within 2 years, it can be a temporizing solution that avoids urethral manipulation and periprocedural device deactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…This is consistent with other large institutional studies and is less than the rate reported by Moses et al who first described outcomes of this technique. 5 Considering the 5 patients who showed signs of impending erosion (and whom we assume would have progressed to erosion), our adjusted total rate of erosion is 16.3% which is similar to the rate reported previously of 14%. 5 While we are not surprised by the overall rate of erosion, what was unforeseen was that radiotherapy, presence of a penile prosthesis, and the 3.5-cm cuff were not found to be predictors of erosion despite the higher circumferential pressure being applied to the urethra.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is consistent with other large institutional studies and is less than the rate reported by Moses et al who first described outcomes of this technique. 5 Considering the 5 patients who showed signs of impending erosion (and whom we assume would have progressed to erosion), our adjusted total rate of erosion is 16.3% which is similar to the rate reported previously of 14%. 5 While we are not surprised by the overall rate of erosion, what was unforeseen was that radiotherapy, presence of a penile prosthesis, and the 3.5-cm cuff were not found to be predictors of erosion despite the higher circumferential pressure being applied to the urethra.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, revision of the pressure-regulating balloon (PRB) has been seldom described despite its relative ease. [5][6][7] In this study, we describe our long-term outcomes in patients who have undergone PRB exchange with "up-pressurization" to a 71-80 cm H 2 O PRB after prior placement of the standard 61-70 cm H 2 O PRB.…”
mentioning
confidence: 99%
“…While a commonly cited etiology for device failure, there is no standard diagnosis or definition of sub-cuff atrophy. [12][13][14] This creates etiological uncertainty and makes consensus guidelines difficult. 15,16 In the absence of laboratory data to confirm or refute the etiology of sub-cuff atrophy, there continues to exist a pattern of recurrent stress incontinence typically 1 to 2 years after successful continence achievement with an AUS which cannot be attributed to overactive bladder or fluid loss from the device.…”
Section: Discussionmentioning
confidence: 99%
“…They support the idea that the apparent 'waisted' aspect of urethra is less an authentic atrophy than a simple sheathing by a fibrotic capsule which can be removed to release the urethra which would regain its initial aspect. They thus suggest to perform urethrolysis combined with the replacement of the whole device during these revisions while most of the authors so far explored cuff downsizing, tandem cuff placement or exchange of PRB as the main therapeutic option in such patients (16,21,22). These heterogeneous opinions underscore the poor understanding of what really happens to these men with recurrent SUI.…”
Section: -Discussionmentioning
confidence: 99%